Human color constancy based on the geometry of color distributions - Morimoto, T; Kusuyama, T; Fukuda, K; Uchikawa, K (Association for Research in Vision and Ophthalmology, 2021)
The physical inputs to our visual system are dictated by the interplay between lights and surfaces; thus, for surface color to be stably perceived, the influence of the illuminant must be discounted. To reveal our strategy to infer the illuminant color, we conducted three psychophysical experiments designed to test our optimal color hypothesis that we internalize the physical color gamut under various illuminants and apply the prior to estimate the illuminant color. In each experiment, we presented 61 hexagons arranged without spatial gaps, where the surrounding 60 hexagons were set to have a specific shape in their color distribution. We asked participants to adjust the color of a center test field so that it appeared to be a full-white surface placed under a test illuminant. Results and computational modeling suggested that, although our proposed model is limited in accounting for estimation of illuminant intensity by human observers, it agrees fairly well with the estimates of illuminant chromaticity in most tested conditions. The accuracy of estimation generally outperformed other tested conventional color constancy models. These results support the hypothesis that our visual system can utilize the geometry of scene color distribution to achieve color constancy.